Iron Deficiency and Anemia of Inflammation in Tuberculosis: A Systematic Review of the Evidence - Deddy Herman; Rizanda Machmud; Nur Indrawaty Lipoeto (HM Publisher, 2025)
Background: Tuberculosis (TB) remains a major global health problem, with anemia being a frequent comorbidity. Anemia in TB is multifaceted, with iron deficiency and anemia of inflammation (AI) being the most common types. This systematic review aims to synthesize the evidence on iron deficiency and AI in TB, their prevalence, impact on outcomes, and management strategies. Methods: A systematic search of PubMed and ScienceDirect databases was conducted for articles published in the last 10 years. Observational studies examining the prevalence, types, and impact of anemia on TB outcomes were included. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Results: The review included 7 studies involving 1,133 participants. Anemia prevalence ranged from 61% to 89% in TB patients. AI was the predominant type, with iron deficiency also prevalent. Anemia was associated with increased mortality, delayed sputum culture conversion, and impaired TB treatment response. Conclusion: Anemia, primarily AI and iron deficiency, is highly prevalent in TB and negatively impacts treatment outcomes and survival. Effective management of anemia is crucial for improving TB outcomes. Further research is needed to optimize diagnostic and treatment strategies for iron deficiency and AI in TB.